Outcome of 2000 Cases of Phacoemulsification - Badr-ud-din Athar Naeem, Badr-ud-din Athar Naeem; Rabia Bashir, Rabia Bashir; Shahzad Iftikhar, Shahzad Iftikhar; Khawaja Naeem Akhtar, Khawaja Naeem Akhtar; Abrar Raja, Abrar Raja; Rasheed Hussain Jaffri, Rasheed Hussain Jaffri; Mustafa Kamal Akbar, Mustafa Kamal Akbar (Journal of Rawalpindi Medical College, 2007)
Phacoemulsification cases performed at Fauji Foundation Hospital, Rawalpindi. Methods: This study was conducted in the Department of Ophthalmology, Fauji FoundationHospital, Rawalpindi, from October 2004 to March 2007. It comprised 2000 cases of phacoemulsification with intraocular lens (IOL) implantation which were performed at Fauji Foundation Hospital in two and a half years. Variables analysed included patient’s age and sex, pre-existing conditions limiting final visualacuity (VA), and type of anesthesia used. Outcome measures included intra operative and postoperative complications and final visual acuity. Results: Of the 2000 cases, there were 72% female and 28% male patients. 62% of patients were given periocular whereas 38% were operated in topical anesthesia. 15.35% of patients suffered intra operative complications. Intra operative complications were: radial tear in 5% cases, posterior capsular (PC) rent without vitreous loss in 3.45% and PC rent with vitreous loss in 4.85% of patients, iris damage in 0.83%, zonular dehiscence in 0.6% of cases, and nuclear fragment drop in 0.3% of patients. Of total patients, 91% of patients kept their appointment for 8 weeks follow up. Postoperatively corrected visual acuity after elimination of factors reducing best corrected visual acuity (BCVA) was 6/9 or better in 89% of cases. Postoperative complications were seen in 20.83% of patients, which included mild to moderate striate keratitis in 11.98%, mild to moderate anterior uveitis in 4.01%, raised intra ocular pressure (IOP) in 0.73%, wound leakage in 0.3%, ophthalmoplegia in 0.05% and endophthalmitis in 0.10% of cases. Posterior capsular opacification (PCO) was seen in 3.65% of patients in 8 weeks of followup. Post operative astigmatism was from 0 – 4.5 D. Conclusion: Phacoemulsification is much safer, predictable, relatively atraumatic procedure and it provides early rehabilitation. It is associated with more patient as well as surgeon satisfaction.